Analisis Kualitas Website SMKN 2 Tanjung Jabung Timur Menggunakan Metode Webqual 4.0 - Wati, Nila; Nehemia Toscany, Afrizal; Irawan, Beni (LPPM STIKOM Dinamika Bangsa, 2023)
In finding information, we often have difficulty, but with a website, it is easier for us to obtain information, one of which is on an educational website, namely SMKN 2 Tanjung Jabung Timur. Theapurpose of this studyawas toadetermine the qualityaof the website of SMKN 2 Tanjung Jabung Timur by using the webqual (Website Quality) method. The webqual method itself consists of several dimensions, namely usability, informationaquality, and service interactionaquality with quantitativeadata analysisatechniques obtained from thearesults of questionnaires/questionnaires. From thearesults of the f test, it is found that theavariablesausability, informationaquality and service interactionaquality togetherahave an influence on userasatisfaction. Thearesults of the t test show thataeach of these independentavariables alsoahas a significantaeffect on the dependentavariable. So that a recommendationais given based on 3 independentavariables fromawebqual. The recommendationais to add a guide/tutorialapage for the use of the website, the manager to improveathe information on each menuaaccording to their needs, provide chatafacilities or interactive questionaand answerato support thearelationship between websiteausers and agencies. With thesearecommendations, it is expectedato be ableato improve theaquality of the website of SMKN 2 Tanjung Jabung Timur